2020
DOI: 10.3758/s13428-020-01496-z
|View full text |Cite
|
Sign up to set email alerts
|

Iconicity ratings for 10,995 Spanish words and their relationship with psycholinguistic variables

Abstract: The study of iconicity, or the resemblance between word forms and their meanings, has been the focus of increasing attention in recent years. Nevertheless, there is a lack of large-scale normative studies on the iconic properties of words, which could prove crucial to expanding our understanding of form-meaning associations. In this work, we report subjective iconicity ratings for 10,995 visually presented Spanish words from 1350 participants who were asked to repeat each of the words aloud before rating them.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Several studies have inspected the relationship between iconicity ratings and different semantic dimensions, such as concreteness (Hinojosa et al, 2021;Winter et al, 2022) and perceptual experience (Sidhu & Pexman 2018;Winter et al 2017Winter et al , 2022. Perhaps surprisingly, no study to our knowledge has ever assessed the relationship between iconicity ratings and the construct they are expected to measure, namely perceptual resemblance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have inspected the relationship between iconicity ratings and different semantic dimensions, such as concreteness (Hinojosa et al, 2021;Winter et al, 2022) and perceptual experience (Sidhu & Pexman 2018;Winter et al 2017Winter et al , 2022. Perhaps surprisingly, no study to our knowledge has ever assessed the relationship between iconicity ratings and the construct they are expected to measure, namely perceptual resemblance.…”
Section: Discussionmentioning
confidence: 99%
“…We also tested whether our measures were significant predictors of iconicity ratings against a strong baseline of psycholinguistic variables that have been shown to be associated with such construct. Indeed, it has been shown that iconicity ratings are negatively associated with word length (Perry et al, 2015;Winter et al, 2017Winter et al, , 2022, log frequency (Perry et al, 2015(Perry et al, , 2018Winter et al, 2017Winter et al, , 2022, age of acquisition (Perry et al, 2018;Winter et al, 2022), concreteness (Hinojosa et al, 2021;Winter et al, 2022), and contextual diversity ; furthermore, they are positively correlated with perceptual experience (Sidhu & Pexman, 2018;Winter et al, 2017Winter et al, , 2022. In our analyses, we included these measures as covariates, to test the predictive power of our metrics while controlling for other possible confounds.…”
Section: Analysesmentioning
confidence: 99%
“…Many dialectal variants of Spanish can be distinguished alongside its large geographical distribution that mainly encompasses Spain and the Americas. Although there is a growing corpus of psycholinguistic research in Spanish developed since the late 1980s and early 1990s (see, for instance, Carreiras et al, 1993;Cuetos & Mitchell, 1988), most normative studies for frequency, word association, affective and other lexical properties refer to Iberian Spanish, the standard variant spoken in Spain (see for instance Fernández et al, 2012;Hinojosa et al, 2021;Stadthagen-Gonzalez et al, 2017), with the notable exception of Aguasvivas et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…It positively influences language learning during infancy (Imai and Kita, 2014; Massaro and Pearlman, 2017; Perniss and Vigliocco, 2014; Perry et al, 2018; Sidhu et al, 2022), and bears a clear relationship with age of acquisition in spoken (e.g. Hinojosa et al, 2020; Perry et al, 2015) and signed languages (e.g. Caselli and Pyers, 2017; Thompson et al, 2012; Vinson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%